2011
DOI: 10.1108/02632771111157169
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between values and workplace: an exploratory analysis

Abstract: Purpose -There exists limited research directly highlighting the relationship between value preference and its association with people's expectations from the workplace. Studying personal value preference is important because a substantial body of research indicates that a specific pattern of value orientations predicts world views, and, hence, it may predict behavior in the workplace. Based on the above-mentioned assumptions, the present study aims to explore the impact of value preferences on the meaning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…In addition, the results indicate a significant negative relationship between self-enhancement values and ethical decision-making. Singh et al (2011) analyse the relationship between value preference and people's expectations from the workplace. The study proposes that value preferences will have a significant impact on the meaning of workplace and values preferences are likely to differ across national culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the results indicate a significant negative relationship between self-enhancement values and ethical decision-making. Singh et al (2011) analyse the relationship between value preference and people's expectations from the workplace. The study proposes that value preferences will have a significant impact on the meaning of workplace and values preferences are likely to differ across national culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, there are a number of variables that may be important to control for when looking at the differences in individual and work values. Lyons and his colleagues (2006) found that demographic variables, such as gender, age, and education, were significantly related to individual values, suggesting that these variables may have more potential to differentiate people on the basis of their individual values than does sector (Lyons et al, 2006;Singh, Bhandarker, Rai, & Jain, 2011). Chusmir and Parker (1991) found that while women and men managers reported similar work values, their individual value rankings were significantly different.…”
Section: Demographic and Job Factorsmentioning
confidence: 93%
“…In organizational literature, the studies on 'work values' and its differentiation of values as intrinsic and extrinsic work values have similarities with the concept of meaning of work. Work values have been defined as the outcomes people desire and feel they should attain through work (Singh, Bhandarker, Rai, & Jain, 2011;Twenge, Campbell, Hoffman, & Lance, 2010). However, work values refer to what an individual ideally desires from work.…”
Section: Personal Meaning Of Workmentioning
confidence: 99%
“…In a recent Indian study, Singh et al (2011) found that with increase in education, people were found to give less emphasis on security and greater emphasis on personal growth. Personal growth here refers to an orientation towards continuous self-development and enhancement of personal skills.…”
Section: Determinants Of Meaning Of Work Presence Of Choicementioning
confidence: 99%
See 1 more Smart Citation